PEMANFAATAN TEPUNG TEMPE PADA PEMBUATAN KERUPUK SAGU - Hamzah, Faizah; Herawati, Netti; ', Syahrial (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The aim of this study was to determine the effect of tempeflour and obtain a formulation that was elected in the manufacture of sago crackers based on quality standards cracker (SNI 01-2713-1999). This study was conducted experimentally by using Completely Randomized Design (CRD) with four treatments and four replications. The treatment in this study was K1 (sago starch : tempeflour100% : 0%), K2 (sago starch : tempeflour 90% : 10%), K3 (sago starch : tempeflour 80% : 20%) and K4 (sago starch : tempeflour 70% : 30%). Data were analyzed statistically using ANOVA and tested further by DNMRT at 5%. The results showed that the addition of tempeflour in the manufacture of sago crackers different in each treatment significantly affected the moisture content, ash content, protein content, flower power as well as evaluating the sensory descriptive and hedonic overall. Sago crackers chosen in this study is a cracker K3 (sago starch : tempeflour 80% : 20%), with a water content of 7,60%, 1,37% ash content, protein content of 5,92% and ranges from 41,24% flower power to the characteristicsslightlybrowncolored, flavoredtempe, tasteless tempeand crispas well asthe overallpreferredpanelists. Keywords: Crackers sago, sago starch, tempeflour.